The Relationship Between Types of Antenatal Education and Contraceptive Used at Tabanan Regency - Ni Wayan Ariyani; Luh Gede Sri Rejeki; Ni Made Dwi Mahayati (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2024)
Mother's knowledge about postpartum contraception can begiven during antenatal education. Antenatal education is theprovision of knowledge to pregnant women provided by health workers. Antenatal education can be given during classes for pregnant women or face-to-face or at interviews. The aim of the study was to determine whether there was a relationship between the type of antenatal education and the use of postpartum contraception at the UPTD Health Center Marga I, Tabanan Regency. Analytical research design, with a cross sectional approach. The sample size of 56 mothers who gave birth more than 42 days to three months was taken by purposive sampling. Data analysis used the chi-square test. The results of the study showed that 18.2% of women who attended interviews used postpartum family planning did not attend 81.8%, mothers who attended classes for pregnant women used postpartum family planning 23.5% who did not use 76.5%, attended interviews and classes for pregnant women using postpartum family planning 52.9% who did not use 47.1%. The conclusion is that there is a relationship between the type of antenatal education and the use of postpartum contraception at the Marga I Health Center in Tabanan Regency with a p value of 0.049. Providing postpartum family planning education in health facilities should be given during interviews and classes for pregnant women.